(untitled) - T G H. James (Cambridge, Massachusetts, 1983)
The book offers a very representative survey of the whole field, from the small primituve figurines of predynastic times (before 3100 BC) to the veristic portrait heads of the Graeco-Roman period (after 332 BC). It describes many of the finest sculptures in the collections, most of which can be seen in the Egyptian Sculture Gallery
Keywords: sculpture, ancient,sculpture, egyptian